Analysis of the Spread of Covid-19 Worldwide: Difference and Similarity - Jossou, Thierry Rock; Chauiyakh, Oussama; Et-tahir, Aziz; Kettani, Kamal; Medenou, Daton (Archives of Clinical and Biomedical Research, 2022)
Background: Today, the world faces a global health challenge caused by COVID-19, but its lethal effect varies from one country to another. Indeed, the COVID-19 does not seem to have the same gravity and lethality wherever transmission focus and chains exist. With COVID-19 epidemic’s progression, measures to stem its propagation are more and more drastic and numerous. Some were taken in a hurry; others are the result of feedback. Did the multiple measures taken to fight the coronavirus have to be adapted to the local specific conditions of each country? In this work, a review of measures taken to stop this pandemic propagation will be first proposed as well as their impacts analysis. It will also provide an overview of COVID-19 levels of vulnerability depending on the disposals and measures taken to fight this virus which differs from one country to another and sometimes overlap. In a second step, we will relate the disparities’ reasons of the lethality rate which must be interpreted with precaution, based on the 10,000 people scale’s demographic rate considered to be reasonable far from any overbidding or chaotic overestimation. The scenarios studied keep into account a wide range of standards and measures adopted, such as: health system’s condition (medical infrastructure, joblessness allowance, etc.), socio-economic development, epidemics’ propagation mode (confinement, age, population density, etc.) and in particular reactivity in measures’ taking (borders’ closing, a mask taking and wearing obligation, distancing, etc.). The choice of France as a reference to compare the different cases is not harmless since it allows comparisons with countries of the same rank at the economic, demographic, social and geographic level, and also with other countries presenting differ